Development of the Seamless Healthcare System, Phan Hospital, Chiang Rai Province - Janjit, Thikamporn; Rattanavichai, Thanyaporn; Poolsawat, Oranong; Praditsathaporn, Chanita (Area Based Development Research Journal, 2020)
The objective of this research is to develop a seamless healthcare service system networking for Phan Hospital, Phan district, Chiang Rai province. The implementation was from October 2014 to September, 2019. Two groups of key informants participated in the study: 1) The service development team consisting of 22 nurses, physiotherapists, nutritionists, and 3 administrators, 2) The service recipients group consisting of 26 Village Health Volunteers (VHV), Community Leaders (CL), and Local Leaders (LL) and 53 patients and caregivers from the service recipients of Phan Hospital. The development of the seamless healthcare service system of Phan Hospital consisted of 1) The seamless healthcare service system under the work of the multidisciplinary, 2) The system of discharge planning of patients among the personnel in the hospital, Sub-district Health Promoting Hospital, community health center, and caregivers, 3) Data referral system and counseling system via VDO call and Line Application, and 4) Material support system, devices that facilitate the disbursement of medicines and medical supplies for patient care. The case managers and Hospital Homeward Working Committee are the links under the conceptual framework of knowledge management and knowledge exchange forum. The implementation resulted in a decreasing number of outpatients. The patient costs could be reduced. The patients received the services as if they were relatives, leading to patient’s satisfaction and stronger bonds with the hospital. Finally, in return, the health personnel were validated professionally.